Lorentz and "apparent" transformations of the electric and magnetic fields - Ivezić, Tomislav, inženjer fizike (Array, 2008)
Summary: It has recently been proved in the tensor formalism and the Clifford, i.e., geometric, algebra formalism that the usual transformations of the three-dimensional (3D) vectors of the electric and magnetic fields differ from the Lorentz transformations (boosts) of the corresponding 4D quantities that represent the electric and magnetic fields. In this paper, using geometric algebra formalism, this fundamental difference is examined representing the electric and magnetic fields by bivectors and 1-vectors